The Effect of Economic Change and Elite Framing on Economic Preferences: A Survey Experiment - Paul Marx; Gijs Schumacher (Institute for the Study of Labor (IZA), 2014)
An unresolved question in political science is how economic downturns affect citizens' economic left-right preferences. Existing observational studies fail to isolate the effect of economic conditions and the effect of elite framing of these conditions. We therefore designed a survey experiment to evaluate how economic change in conjunction with different elite frames impact on citizens' preferences for economic policies. We hypothesise and demonstrate that the effects of these frames differ by income group and partisanship. Our survey experiment carried out in the UK demonstrates that poor economic prospects motivate support for unemployment benefits vis-à-vis deficit reduction. Emphasis on government debt and deficits increases support for the latter policy option. Also, we find support for the hypothesis that partisans are less responsive to the economy than independents.
Keywords: D72; Z18; 330; economic preferences; economic crises; elite framing; survey experiment; UK